Responsible Leadership, Work Engagement and Meaningful Work Relationship in Organizations - Gülbahar, Yasemin (İşletme Araştırmaları Dergisi, 2025)
Purpose – While traditionally, the workplace primarily focused on fulfilling individuals' basic needs, there is a growing recognition of the importance of meeting psychological needs as well. Employees now desire well-being, satisfaction, and a sense of meaning in their work lives. Factors such as meaningful work, job resources, and leadership styles play a crucial role in fostering these positive experiences and influencing organizational commitment. Therefore, this study aims to investigate the impact of responsible leadership and meaningful work on work engagement among female employees in the automotive sector within the Ankara Organized Industrial Zone (OSTİM). Specifically, the study will examine the direct effects of responsible leadership on work engagement and the mediating role of meaningful work in this relationship. This focus on responsible leadership stems from its increasing recognition as a critical aspect of responsible leadership that considers the needs of various stakeholders while promoting individual and organizational well-being. Design/methodology/approach – This research was conducted in Ankara Organized Industrial Zone (OSTIM) in Turkiye with a sample of 242 people. Findings – It was concluded that responsible leadership positively impacts work engagement and that meaningful work mediates this relationship. Discussion – This study examined the impact of responsible leadership on work engagement, with a specific focus on the mediating role of meaningful work, among female employees in the automotive sector within the Ankara Organized Industrial Zone (OSTİM). The findings indicated a significant positive relationship between responsible leadership and work engagement, and further revealed that meaningful work partially mediated this relationship. These results offer valuable theoretical contributions and practical implications for organizations and managers.